Upaya Upaya Meningkatkan Aktivitas dan Hasil Belajar Matematika melalui Model Pembelajaran Novick pada Siswa Kelas VIII MTs Al Jauhar - Umi Hidayah; Afghohani, Afif; Erika Laras Astutiningtyas (Universitas Veteran Bangun Nusantara, 2024)
Students have different characteristics and backgrounds. One way for teachers to meet the learning needs of students who have different characteristics is to apply the Novick learning model. This research aims to increase student activity and learning outcomes through the Novick learning model on flat-sided geometric material. This research is classroom action research (PTK) with four stages, namely planning, action, observation, and reflection. The subjects in this research were 24 students in class VIII A of MTs Al Jauhar. The research results showed an increase in the weight value of student activities in the initial condition of 11 or 24,75 to 20 or 45,00% in cycle I, then increased to 27 or 60,75% in cycle II, and again increased to 35 or 97,22% in cycle III. Then from the results of the average value of the conditions initial 62,1 to 70,41 in cycle I, then increased to 73,75 in cycle II, and increased again to 85 in cycle III. This research appears to be a process of increasing activity and results from student learning from before the action, after the action in cycle I, cycle II, and cycle III in learning using the Novick learning model in the classroom after going through 3 cycles. The results of this research state that there is an increase in student activity and learning outcomes when implementing the Novick learning model.